PENGOLAHAN BEKASAM IKAN SEPAT (Trichogaster trichopterus) DI DESA SUNGAI BESAR KECAMATAN KARANG INTAN KABUPATEN BANJAR PROVINSI KALIMANATAN SELATAN - Zuraida; Yayuk Minta Wahyuningsih (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Bekasam Fish Sepat and Samu Fish Sepat are one of the names of processed fish products in preserving fresh fish. Bekasam is made from fish that is salted through a fermentation process with salt and rice. Fish that is marinated, and there is also mixed with a sprinkling of roasted or fried rice samu. In addition, there is Bekasam Samu Fish Sepat which only uses salt and is mixed with samu, which is ready to be consumed in just one day. The fish that will be made into bekasam can be any type of fish, but the most popular among Banjar people is bekasam samu river fish, because the results of this fermentation give a distinctive sour taste to the fish, as well as a soft and rich texture. Bekasam has a more chewy meat texture than fresh fish in general, as well as samu fish. Processing Samu fish sepat takes less time, not in days like bekasam, because this samu fish does not produce a sour taste but a savory taste and the aroma of the samu is dominant. The difference is in the processing time and the taste and aroma of the fish produced only. This activity is also a real step in an effort to process fresh fish so that it lasts a long time by preserving it in a traditional and simple way. It is hoped that participants can gain very good knowledge to be applied when fish that are not valuable during the abundant season if processed properly will be able to provide added value economically and socially, especially to meet the nutritional needs of families and communities